2014
DOI: 10.1007/s12262-014-1043-4
|View full text |Cite|
|
Sign up to set email alerts
|

Types of Renal Calculi and Management Regimen for Chinese Minimally Invasive Percutaneous Nephrolithotomy

Abstract: Strict selection of patients for minimally invasive percutaneous nephrolithotomy could effectively improve the success rate of surgery. This study aimed to understand the required skills and the efficacy of mini-PCNL in the treatment of five types of upper ureteral calculi. Data collected after X-ray analysis and B mode ultrasound from 633 patients with upper ureteral and renal pelvis calculi who underwent B ultrasound-guided lithotomy was reviewed, including the following: type I, upper ureteral or renal pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Since this technique is not explicitly mentioned by the current guidelines, the authors did a thorough review of the literature and meta-analysis, being able to demonstrate the superiority of this combined approach in terms of stone-free rate, operative time, complications and the number of access tracts, an important limit of percutaneous surgery. The authors conclude that for complex stones, the combined access is superior to PCNL alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this technique is not explicitly mentioned by the current guidelines, the authors did a thorough review of the literature and meta-analysis, being able to demonstrate the superiority of this combined approach in terms of stone-free rate, operative time, complications and the number of access tracts, an important limit of percutaneous surgery. The authors conclude that for complex stones, the combined access is superior to PCNL alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MIP nephroscope, due to its small size, passes easily in to the proximal ureter and is particularly well suited for the [38] 191 -Small vs large 84 23 Long et al [8] 163 -Ureteric stones 96 0 (major) Zhan et al [39] 109 -Supine vs prone 89 -Hu et al [40] 1 368 --82 20 Gu et al [41] 611 --82 6 Xu et al [42] 1 200 843 mm 2 UTI vs no UTI -7.6 Zhu et al [43] 450 -II vs USS 80 -Akbulut et al [44] 182 -Obese vs non-obese 71 -Zeng et al [45] 146 22 mm Super-mPCNL 90 13 Zhao et al [46] 145 -1-vs 2-stage mPCNL 83 -Agrawal et al [47] 120 --99 0 (major) Liu et al [48] 105 -Single-vs multi-tract 50 30 II, image intensifier; USS; ultrasound scan. *Stone size listed as either maximum dimension, or volume.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional PCNL surgery generally involves pre-placing a ureteral catheter and injecting normal saline into the renal pelvis or initiating a continuous drip of saline to create artificial hydronephrosis. However, many studies have reported the disadvantages of this approach [ 11 12 ]. For instance, an anterograde position of the indwelling double-J stents at the end of the surgery has shortcomings and increases the operation time, especially when an emergency happens like massive bleeding and the operation cannot be stopped immediately.…”
Section: Introductionmentioning
confidence: 99%